FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN KAS (Students' Journal of Accounting and Banking, 2012)
The Perpouse of this research is to identify of Return on Investment (ROI), Current Ratio (CR), Earning Per Share (EPS) Debt to Total Assets (DTA) and Cash Ratio (CRo) that influence Cash Dividend.Population in this research is all peripatetic company LQ-45 which enlist in Effect Exchange Indonesia (BEI) Year 2007-2010. Technique intake of sampel use technique of purposive sampling. Technique analysis sampel the used is linier regression.Research result indicte that Return on Investment (ROI), Current Ratio (CR), Earning Per Share (EPS) have an effect positive and significant to Cash Dividend. While variable of Debt to Total Assets (DTA) an dCash Ratio (CRo) not have an effect to Cash Dividend.Keywords: Return on Investment (ROI), Current Ratio (CR), Debt to Total Assets (DTA), Earnings Per Share(EPS), Cash Rasio(Cro), Cash Dividend